Community Knowledge about Medicinal Plants in Samudra Jaya and Pahlawan Setia Villages, North Bekasi - Reza Anindita; Syahla Haediningrum; Maya Uzia Beandrade; Intan Kurnia Putri; Dede Dwi Nathalia; Melania Perwitasari; Nofria Rizki Amalia Harahap; Chandra Rahmadi (The Ethnobiological Society of Indonesia, 2024)
The purpose of this study was to describe the knowledge and use of medicinal plants by the people of Samudra Jaya and Pahlawan Setia Villages, Tarumajaya Sub-district, North Bekasi. The research design is an exploratory survey and observation. The sample numbered 119 people, consisting of 69 people representing Pahlawan Setia Village and 50 people representing Samudra Jaya Village. The sampling technique used purposive random sampling. Variables in this study include the value of community knowledge about medicinal plants, the value of community knowledge about the use of medicinal plants, the organs of plants that are often used, the percentage of how to use medicinal plants, and the families and species of plants used as medicine. Data analysis was carried out descriptively. The results showed that the value of community knowledge about medicinal plants was 354 (classified as good), the value of community knowledge regarding the use of medicinal plants was 300.4 (classified as good), the organs of plants that were often used as medicine were leaves (95%), the percentage of how to use medicinal plants are more dominant by boiling (91%), there are 19 families with 22 species of plants used as medicine. The family includes Zingiberaceae, Polygonaceae, Liliaceae, Acanthaceae, Oxalidaceae, Talinaceae, Crassulaceae, Rubiaceae, Lamiaceae, Piperaceae, Basellaceae, Euphorbiaceae, Solanaceae, Caricaceae, Menispermaceae, Asparagaceae, Zingiberaceae, Myrtaceae, Rutaceae, Leguminosae, and Moraceae, with plant species: kunyit (Curcuma domestica), jambu biji (Psidium guajava), sirih hijau (Piper betle), mengkudu (Morinda citrifolia), lidah buaya (Aloe vera), brotowali (Tinospora crispa), sambiloto (Andrographis paniculata), saga (Abrus precatorius), jahe (Zingiber officinale), belimbing wuluh (Averrhoa bilimbi), cocor bebek (Kalanchoe pinnata), ciplukan (Physalis peruviana), jeruk nipis (Citrus aurantiifolia), jarak pagar (Jatropa curcas), kumis kucing (Orthosiphon aristatus), gondola (Basella rubhalin), pepaya (Carica papaya), ginseng jawa (Talinum paniculatum), telang (Clitoria ternatea), getih-getihan (Rivina humilis), tin (Ficus carica), and suji (Dracaena angustifolia). The study concludes that the results of survey scores regarding the knowledge and use of medicinal plants by the people of Samudra Jaya and Pahlawan Setia Villages are classified as good. The species of medicinal plants that are most widely used are the Zingiberaceae family, with local names of plant species, namely jahe and kunyit. Both plants are used by boiling to relieve menstrual pain and treat bloating and colds.